The Effect of Green Accounting and Environmental Performance on Financial Performance of Manufacturing Companies 2020–2024 - Leli Wijaya Sari; M. Imam Sundarta; M. Anwar Masruri (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2026)
The rapid development of the industrial sector has contributed positively to economic growth; however, on the other hand, it also has the potential to create various environmental problems resulting from companies’ operational activities. One of the efforts that companies can undertake to minimize these negative impacts is by implementing green accounting and improving environmental performance optimally. This study was conducted to determine the extent of the influence of green accounting and environmental performance on the financial performance of manufacturing companies in the consumer non-cyclicals subsector listed on the Indonesia Stock Exchange during the 2020–2024 period. The data collection method used purposive sampling, while the data analysis method employed multiple linear regression analysis, resulting in 60 research data samples processed during the 2020–2024 period. This study used secondary data obtained from companies’ annual reports, sustainability reports, and PROPER rating data published by the Ministry of Environment and Forestry. The analytical tool used in this research was SPSS version 27. The results of the multiple linear regression analysis indicate that: (1) green accounting has no effect on the company’s financial performance, (2) environmental performance has a significant positive effect on the company’s financial performance, and (3) simultaneously, green accounting and environmental performance have a significant effect on the company’s financial performance.